Numerical analysis of prestressed hollow core slabs under long term loading - S. R. Pereira; J. M. Calixto; T. P. Bortone (Revista IBRACON de Estruturas e Materiais)
This paper presents a numerical analysis of prestressed hollow core slabs under long term loading. The model considers the time dependence of material and rheological properties in order to predict the actual stage of displacements, strains and stresses. It also takes into account load changes. For the analysis, each slab is divided in a finite number of bar elements, in which the cross section is described in concrete elements, parallel to the flexural axis, and prestressed steel elements. For the results evaluation, the effective concrete area is considered. The numerical results are compared with experimental tests performed on two series of prestressed hollow core slabs. Each series had a different geometry, rate and distribution of prestressing strands. Mid-span displacements were evaluated up to 127 days after initial loading. Good correlation was achieved with both series at and below the service load level.